Sumbangan Konsep Otentisitas Martin Heidegger bagi Praksis Dialog Interreligius: Upaya Mendukung Moderasi Beragama di Indonesia - Ilham, Kristoforus Juliano; Riyanto, F.X. Eko Armada (Kamaya: Jurnal Ilmu Agama, 2023)
Martin Heidegger's concept of authenticity, which is the focus of this article, has made a significant contribution to the practice of interreligious dialogue and religious moderation in Indonesia. The reason is because this concept offers authentic humans in every religion in Indonesia. An authentic human being is identified as a person who is able to see himself as a whole, is able to take responsibility for his existence, and is able to understand himself as a human being who truly lives in the world without being dominated and determined by other people. The aim to be achieved in this research is to form and develop authentic religious subjects in every religion in Indonesia. By using a qualitative descriptive method in the form of reviewing various scientific sources that are in accordance with this discourse, this paper succeeded in finding that Martin Heidegger's concept of Authenticity is important to instill in every religion in Indonesia in forming and developing religious subjects who take part in dialogic interreligious dialogue and support moderation. religion in Indonesia. The novelty of this article is that Martin Heidegger's concept of Authenticity is relevant to religious life in Indonesia, both in the practice of interreligious dialogue and in supporting religious moderation in Indonesia.